Knowledge and attitudes about human papillomavirus infection and prevention methods among medical science students in Novi Sad, Serbia: a cross-sectional study - Nikola Denda; Nemanja Maletin; Aleksandar Rašković; Dušan Prodanović; Zoran Golušin; Biljana Vučković; Marko Nemet; Milica Paut Kusturica (BMC Public Health)
Abstract Background It is estimated that more than 80% of people are infected with human papilloma virus (HPV) at some point in their lives. Knowledge about HPV infection and methods of its prevention is important for society as a whole. Medical students as future healthcare workers must be thoroughly informed about HPV infection in order to properly participate in the promotion of its prevention. The aim was to examine the knowledge and attitudes in relation to previous education about HPV infection and prevention methods. Methods A cross-sectional study was conducted among undergraduate students at the Faculty of Medicine in Novi Sad (MFNS). The study covered all study programs and was conducted in the period from 1 to 30 November 2023, using a specially created survey questionnaire for the purposes of this research. Results 1760 surveys were collected, representing 70.4% of the total number of MFNS students. In the past year, only 26% of respondents attended some kind of education about HPV infection/vaccine. Statistical significance was observed in the difference between the responses of students who attended education in comparison to those who did not attend education in the past year (75.5% versus 63.3%, p < 0.001). Students who stated that they plan to get vaccinated in the following period answered the questions correctly in a higher percentage (87.5% versus 80.1%, p = 0.01). Conclusions Students of the Faculty of Medicine in Novi Sad, as future healthcare workers, demonstrated certain knowledge and demonstrated right attitudes. Students who attended education about HPV infection and methods of prevention had more correct answers, as did students who plan to get vaccinated in the future.